Dietary trends and obesity in Saudi Arabia - Alhusseini, Noara; Alsinan, Nawra; Almutahhar, Shahad; Khader, Majd; Tamimi, Rawand; Elsarrag, Mazin Ibrahim; Warar, Rabah; Alnasser, Sara; Ramadan, Majed; Omair, Aamir; Aouabdi, Sihem; Saleem, Rimah; et al. (Frontiers in Public Health, 2024)
Introduction Dietary habits in Saudi Arabia have been shifting toward the Western diet, which is high in fat, salt, and sugar, leading to a high obesity rate. Different dietary strategies such as the Ketogenic Diet (KD), Intermittent Fasting (IF), Gluten Free Diet (GFD), and Calorie Restriction Diet (CRD) have shown an influential role in weight loss. This study aimed to compare trending diets and correlate different types of diet with obesity and lifestyle among adults in Saudi Arabia. Methods A cross-sectional study was performed on Saudis and non-Saudis over 18 years old. We used convenience sampling, an online questionnaire distributed via social media channels, including WhatsApp, LinkedIn, and Twitter. SPSS 28 software was applied for data analysis. The chi-square test was used to determine associations between different variables. Statistical significance was considered at a value of p less than 0.05. Results Most participants were females residing in the Eastern and Central regions of Saudi Arabia. Although most do not follow any dietary plan, they exhibited acceptable exercise and lifestyle. The minority of the study population followed different types of diet plans, such as KD, IF, and GFD. The purpose of most of the participants who have used these strategies was for weight loss but failed to sustain the dietary plan for more than 1 month. Conclusion Obesity remains a challenging issue in Saudi Arabia. Adherence to dietary regimes could help in controlling obesity. Increasing the awareness of the benefits of each dietary plan for health, choosing the appropriate one, and sustaining a balanced nutrition pattern.